2019
DOI: 10.1088/1742-6596/1391/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of skyrmion shape deformation under uni-axial stresses

Abstract: Skyrmion is a topologically stable spin texture and expected to be applied to the future computer memory. On the semiconductors such as FeGe and MnSi, the skyrmion configuration is stable in the sense that it is not strongly affected by a small variation of external stimuli such as temperature, magnetic field etc. In recent experiments, it was reported that the skymion shape is deformed from isotropic (or circular shape) to anisotropic (or elliptic shape) by an external mechanical stress. This shape deformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…where FMI and DMI energies S FM and S DM are given in two different combinations denoted by model 1 and model 2 [39] (see Appendix A)…”
Section: B the Hamiltonian And A New Variable For Mechanical Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…where FMI and DMI energies S FM and S DM are given in two different combinations denoted by model 1 and model 2 [39] (see Appendix A)…”
Section: B the Hamiltonian And A New Variable For Mechanical Strainsmentioning
confidence: 99%
“…In this paper, using Finsler geometry (FG) modeling, which is a mathematical framework for describing anisotropic phenomena [36][37][38], we study two possible models for the deformation of skyrmions and magnetic stripes [39]. In one of the models, the FMI coefficient is deformed to be λ x = λ y , while DMI is isotropic, and in the other model, the DMI coefficient is deformed to be D x = D y while FMI is isotropic.…”
Section: Introductionmentioning
confidence: 99%
“…The skyrmion can also be deformed by altering the material parameters of the system. Koibuchi et al 28 calculated the skyrmion deformation due to mechanical stresses that modulate the DMI, while Hu et al 29 have seen that elliptical skyrmions can be induced when there is an anisotropic strain. Mehmood et al 30 showed that the skyrmion shape can be manipulated by changing the perpendicular magnetic anisotropy.…”
Section: Introductionmentioning
confidence: 99%